Post-marketing study design to evaluate the effectiveness of the 9-valent and 4-valent HPV vaccines on serious HPV-related cervical disease in China - Yu Yang; Liang Zhang; Susanne Hartwig; Peng Jiang; Houyu Zhao; Ruogu Meng; Zhike Liu; Zuoxiang Liu; Keqin Ding; Xuedan You; Carol Koro; Guozhang Xu; et al. (Taylor & Francis Group, 2024)
The 4-valent (4 v) and 9-valent (9 v) human papillomavirus (HPV) vaccines are approved in China for females aged 9-45 years. However, the real-world impact of 4vHPV or 9vHPV vaccination for the prevention of high-grade cervical disease in Chinese women is lacking. Two post-marketing surveillance studies will be conducted to measure the occurrence of high-grade cervical lesions in Chinese women who had received ≥1 dose of the 4vHPV (aged 20-45 years) or 9vHPV (aged 16-26 years) vaccine in Ningbo, China. Vaccination data will be extracted from the Ningbo Regional Health Information Platform (NRHIP) from the date of the first 4vHPV (January 9, 2018) or the first 9vHPV (January 25, 2019) vaccination to March 31, 2021. The primary 4vHPV and 9vHPV vaccinated cohorts will include women vaccinated per protocol. The 4vHPV/9vHPV vaccinated test-negative (cervical HPV negative; ThinPrep cytology test negative) and corresponding matched unvaccinated HPV test-negative sub-cohorts will also be assessed. Outcomes will be the occurrence of new-onset cervical intraepithelial neoplasia grade 2/3, adenocarcinoma in situ, and invasive cervical cancer. This study aims to demonstrate that such a methodological approach is feasible and can be used to assess the impact of HPV vaccination in other regions across China.